The Problems of Providing Information in the Management of the Media Industry Enterprises - Леся Андріївна Пунчак; Ольга Михайлівна Барзилович (Технологія і техніка друкарства, 2016)
In modern economic conditions, managerial decisions of managers of enterprises in the media industry and their structural subdivisions are taken at risk. Risk parameters are reduced if the guidance is based on prior experience and market information. Rapid changes in the marketing environment of the enterprise reduce the value of previous experience, which complicates forecasting and increases the risk of making managerial decisions.